Psychiatric rehabilitation in the hospital setting - one year follow-up of patients with schizophrenia - Švab, Vesna (Zdravstveno varstvo, 2007)
Background: In recent years, the majority of long-term hospitalized patients with schizophrenia, who had no relapse during standard psychiatric management,were discharged from the Ljubljana Psychiatric Hospital because of increased number of admissions and limited hospitalization length. To ensure safest possible discharge, a hospital rehabilitation and planned discharge programme has been set up for patients requiring long-term care and frequent rehospitalizations Methods: Forty-one (41) long-term and frequently admitted patients with schizophrenia were included in the study. One-year follow up involved monitoring of their needs, clinical status, global functioning and quality of life. A rehabilitation programme was designed and tailored to the characteristics and needs of the patients studied. In addition to standard psychiatric treatment, detailed information on the disease was given to the patients and their families. They were included in social skills training, anda management plan was prepared for each of them. Results: Within one year,negative symptoms of the disease were reduced significantly and the patients became more satisfied with the quality of their life. Most of their social needs, however, could not be addressed . Conclusions: Individually adjusted programmes of hospital psychiatric rehabilitation for patients suffering from most resistant forms of schizophrenia, and inclusion of their family or relatives in their rehabilitation significantly improved disease outcomes in these patients.
Keywords: bolnišnično zdravljenje; psihiatrično zdravljenje; rehabilitacija; shizofrenija; vocational rehabilitation